Teachers’ Perspective of Grammarly as an Online Grammar Checker to Improve Writing Skill - Isyabella Isyabella; Anita Dewi Ekawati (UICELL, 2022)
Writing is one of the important skills in English. Using correct grammar and spelling in writing English is an important aspect. There are many online spelling and grammar checking tools available today to improve the quality of your writing. In this modern era, writing plays an important role in real life. Teachers need more tools because they need to help them write and evaluate their writing. In this study the authors used Grammarly as an online grammar checking tool to check grammar, punctuation and spelling in written English. This study aims to determine the teacher's perspective on Grammarly as an online grammar checker tool to improve writing skill. This study uses a qualitative method with a survey design. The instruments in this research were questionnaire and interview to collect data.The population in this research were 20 English teachers who were given questionnaire, then the researcher took 13 teachers to be interviewed. The researcher use triangulation technique to analyze the data that has been collected. The results showed that the teachers gave a positive response to Grammarly as an online grammar checking tool. Teachers are helped by the Grammarly feature which can help check their English writing. The teachers believed that the results of the Grammarly check were accurate and reliable. They become more confident in writing when checked using Grammarly. The error explanation feature in Grammarly also adds to their insight in writing English. However, teachers also feel the lack of features of the limited premium version which requires payment to access Grammarly's premium features. Keywords: Teacher perspective, Grammarly, writing